Anomalies of Ionic/Molecular Transport in Nano and Sub-Nano Confinement - Wang, Miao; Hou, Yaqi; Yu, Lejian; Hou, Xu (Nano letters, 2020)
Understanding and exploring the transport behaviors of ions and molecules in the nano and sub-nano confinement has great meaning in the fields of nanofluidics and basic transport physics. With the rapid progress in nanofabrication technology and effective characterization protocols, more and more anomalous transport behaviors have been observed and the ions/molecules inside small confinement can behave dramatically differently from bulk systems and present new mechanisms. In this Mini Review, we summarize the recent advances in the anomalous ionic/molecular transport behaviors in nano and sub-nano confinement. Our discussion includes the ionic/molecular transport of various confinement with different surface properties, static structures, and dynamic structures. Furthermore, we provide a brief overview of the latest applications of nanofluidics in membrane separation and energy conversion.